Fixed-Point Results on Complete G-Metric Spaces for Mappings Satisfying an Implicit relation of New Type - Patriciu, A.-M.; Popa, V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We prove general fixed-point theorems (generalizing some recent results) in a complete G-metric space.